Effect of idiopathic thoracic scoliosis on the tracheobronchial tree. Issue 1 (25th March 2018) - Farrell, James; Garrido, Enrique
Abstract : Introduction: High prevalence of obstructive lung disease has been reported in patients undergoing surgical correction of thoracic scoliosis. Airway narrowing due to spine morphology is analysed as a contributing factor. Methods: Preoperative surgical planning CTs of 34 patients with right-sided thoracic scoliosis (age: 17.6±9.0) were retrospectively analysed and compared with 15 non-scoliotic controls (age: 16.3±5.1). Three-dimensional models of spine and airway lumen were reconstructed. Based on thoracic sagittal profile, patients were divided into hypokyphosis (HypoS: <10°), normal kyphosis (NormS: ≥10° and <40°) and hyperkyphosis (HyperS: ≥40°) groups. Lumen area of bronchi, bifurcation angles and minimum spine–airway distance were measured. Pulmonary function tests were correlated to scoliosis, kyphosis and lumen area. Results: Loss of kyphosis led to proximity between bronchus intermedius (BI) and spine. HypoS (NormS) had lumen area reductions in the right main bronchus of 29% (19%), BI of 45% (23%), right middle lobar bronchus of 46% (32%) and right lower lobe bronchus (RLL7) of 66% (37%), respectively (P<0.05). The lower right superior segmental bronchus was reduced across all scoliotic groups (P<0.05). Airways were displaced caudal by 0.65±0.45 vertebra in patients with scoliosis. Loss of kyphosis correlated negatively with forced expiratory volume in 1 s/forced vital capacity (FEV1 /FVC), FVC/(FVC predicted) and FEV1 /(FEV1 predicted) (P<0.01). Lumen area of trachea, right upper lobar bronchus, BI and RLL7 correlated negatively with FEV1 /FVC. BI and RLL7 narrowing were strong predictors of FVC and FEV1 loss (P<0.001). Conclusions: Right-sided main stem airways are narrowed in HypoS and NormS. Loss of kyphosis leads to narrowing of BI and its trifurcation. FEV1 /FVC correlated negatively with airway narrowing, implying an obstructive element to lung function impairment in patients with scoliosis and hypokyphosis.